PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KOMITMEN ORGANISASI PADA KINERJA SDM KANTOR KESATUAN BANGSA DAN PEMBINAAN POLITIK KABUPATEN BUTON - La Ode Abdul Salam Al Amin (Jurnal Ushuluddin Adab dan Dakwah, 2018)
This study was conducted to determine the hypothesis with the intention to justify or reinforce the hypothesis with the hope that eventually can strengthen the theory that became the foundation to examine how the effect of leadership on Job Satisfaction, how the influence of leadership on Work Effectiveness, how the influence of the Organizational Commitment and Leadership how the leadership of the HR Performance and Organizational Commitment on how to influence human performance on the Office of National Integration and Political Development Kab. Buton. Populations used are all employees of the Authority's office Kab.Buton numbering 56 human resources with a population of 56 at the same time be made respondents.The study was conducted by survey method by distributing koesioner to 56 respondents in the Office of National Integration and Political Development Kab.Buton. The results showed that: 1).There is a positive and significant impact on the job satisfaction variable leadership style of leadership does it mean when both the job satisfaction will increase, so the hypothesis is accepted. 2). There is a positive influence on the performance vaiabel Leadership of Human Resources, Leadership means if either the HR performance will increase, so the hypothesis is accepted. 3). There is not a positive and significant effect on the variable Motivation on Job Satisfaction mean when motivation is high then job satisfaction will increase, so the hypothesis is accepted. 4). There is no positive and significant impact on the performance variables HR Organizational Commitment, Organizational Commitment means if either the HR performance will increase, thus degan hypothesis is accepted. 5). There is a significant influence on the performance of human resources motivation variable, meaning that if either the Motivation HR performance will increase, then the hypothesis is accepted.